1994
DOI: 10.1038/hdy.1994.155
|View full text |Cite
|
Sign up to set email alerts
|

Single locus inheritance and joint segregation analysis of minisatellite (VNTR) DNA loci in brown trout (Salmo trutta L.)

Abstract: Eleven minisatellite (VNTR) DNA loci were examined for Mendelian inheritance and possible linkage relationships in a brown trout family (54 offspring). Analyses of the full progeny set (males and females combined) showed no statistically significant departures from Mendelian expectations at any locus, and no new mutations were observed. However, at one locus, Str-A9, differential segregation (P <0.001) of parental alleles into male and female progeny was recorded. This is indicative of tight linkage between St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Mendelian inheritance having been previously tested in several families (Taggart & Ferguson, 1990b;Prodohl et al, 1994b). Radiolabelling, hybridization and posthybridization washes followed those described in Taggart & Ferguson (1990b) and Pendás et al (1994).…”
Section: Dna Analysismentioning
confidence: 99%
“…Mendelian inheritance having been previously tested in several families (Taggart & Ferguson, 1990b;Prodohl et al, 1994b). Radiolabelling, hybridization and posthybridization washes followed those described in Taggart & Ferguson (1990b) and Pendás et al (1994).…”
Section: Dna Analysismentioning
confidence: 99%
“…Similar results were subsequently reported in other genera: A growth hormone marker was shown to be sex-linked in coho salmon, chinook salmon, and masu salmon, but sex linkage was not conserved in amago salmon (Oncorhynchus rhodurus) and rainbow trout (Forbes et al 1994;Nakayama et al 1999;Zhang et al 2001). Similarly, a minisatellite locus shown to be in tight linkage with SEX in brown trout by Prodöhl et al (1994) was mapped to an autosomal pair in Atlantic salmon (Taggart et al 1995). Interspecific disruption of sex linkage is surprising because extensive conservation of linkage arrangements has been observed for biochemical (Johnson et al 1987) and microsatellite (Gharbi 2001) loci.…”
mentioning
confidence: 99%
“…For example, sex-reversed females of rainbow trout (Oncorhynchus mykiss), chinook salmon (Oncorhynchus tshawytscha), coho salmon (Oncorhynchus kisutch), and Atlantic salmon (Salmo salar) produce all female progeny when crossed with normal females, indicating that females are homogametic XX (Johnstone et al 1979;Hunter et al 1982Hunter et al , 1983Johnstone and Youngson 1984). Subsequent characterization of sex-linked markers has also provided support for male heterogamety in Arctic charr (Salvelinus alpinus), lake trout (Salvelinus namaycush), masu salmon (Oncorhynchus masou), pink salmon (Oncorhynchus gorbuscha), chum salmon (Oncorhynchus keta), brown trout (Salmo trutta), rainbow trout (O. mykiss), coho salmon (O. kisutch), and chinook salmon (O. tshawytscha; May et al 1989;Du et al 1993;Forbes et al 1994;Prodöhl et al 1994;Young et al 1998;Nakayama et al 1999;Sakamoto et al 2000;Devlin et al 2001;Zhang et al 2001;Stein et al 2002).…”
mentioning
confidence: 99%
“…While an extremely variable locus in humans has been shown to have an extremely high mutation rate (Jeffreys et al, 1988), and surely similar loci will be found in other organisms, in general, transmission of VNTR markers has been shown to primarily follow Mendelian inheritance (e.g., Dallas, 1988;Prodohl et al, 1994;Rogstad, 1994a;Arens et al, 1995), with a level of meiotic mutation that is often detectable and high relative to other types of genetic markers (e.g., allozymes, most single-copy RFLP probes). For example, three of 595 VNTR bands (0.5%) transmitted to offspring were non-parental in Brassica rapa L. (turnip; Brassicaceae; Rogstad 1994a), while mutation frequencies of 0.001 for human CAC VNTR marker transmission (Nurnberg et al, 1991) and less than 0.0003 for GATA VNTR marker transmission to the F 2 population from a Lycopersicum esculentum Mill.…”
Section: Introductionmentioning
confidence: 98%